Perancangan Sistem Informasi Kampus Berbasis WAP (Wireless Application Protocol) - Sutariyani . (Indonesian Journal of Networking and Security (IJNS), 2015)
ABSTRACT: Technology Wireless Application Protocol (WAP) can act as a bridge between  internet world with nirkabel world. Second merger of the technology enables to access information which is not depend on information source and location of access. Information is very worthing, because with existence of information can be taken important decisions. Information hardly required by public, so it is necessary a system that capable to save and process all the information of data.Based on ease and the developing of technology cellular telephone with has not existence of campus information systems bases on WAP, based of that the writer builds system application of information of campus which limited to information of campus and builds web admin by exploiting The Technology Wireless Application Protocol with aim to that information of campus can be accessed any time and everywhere also by using cellular telephone and aim to that web admin can add or changes the data.The Research method used bibliography, analysis, scheme, programming, testing and system implementation. Scheme of this system exploits language Wireless Markup Language presenting a web of WAP and PHP with data base MySQL. Data base can be added, edited, vanished, through website while to access it is using cellular telephone and website. Keyword : WAP, WML, databaseABSTRAK: Teknologi Wireless Application  Protocol (WAP) dapat menjembatani jarak antara dunia internet dengan dunia nirkabel. Penggabungan kedua teknologi tersebut memungkinkan untuk mengakses informasi yang tidak tergantung  pada sumber informasi dan lokasi akses. Informasi adalah sesuatu yang sangat berharga, karena dengan adanya informasi  dapat diambil keputusan-keputusan penting. Informasi sangat diperlukan oleh masyarakat, sehingga diperlukan sebuah sistem yang mampu menyimpan dan memproses semua data-data informasi tersebut.Berdasarkan kemudahan dan berkembangnya teknologi telepon seluler serta  belum adanya sistem informasi kampus berbasis WAP kampus yang terbatas pada informasi kampus STMIK-AUB Surakarta dan membangun web admin dengan memanfaatkan Teknologi Wireless Application Protocol yang bertujuan agar informasi kampus bisa diakses kapan pun dan dimana pun dengan menggunakan telepon seluler serta bertujuan agar web admin bisa menambah atau pun mengubah data.Metode penelitian dengan kepustakaan, analisis, perancangan, pemrograman, uji coba dan implementasi sistem. Perancangan sistem ini memanfaatkan bahasa Wireless Markup Language yang menampilkan suatu situs WAP dan PHP dengan basisdata MySQL. Basis data dapat ditambah, diedit, dihapus, melalui website sedangkan untuk mengaksesnya menggunakan telepon seluler dan website.Kata kunci : WAP, WML, basis data